Quantitative real-time PCR of enteric viruses in influent and effluent samples from wastewater treatment plants in Italy - Giuseppina La Rosa; Manoochehr Pourshaban; Marcello Iaconelli; Michele Muscillo (Istituto Superiore di Sanità, 2010)
The prevalence of enteric viruses in wastewater, the efficacy of wastewater treatments in eliminating such viruses, and potential health risks from their release into the environment or by recycling of treated wastewaters, are very important issues in environmental microbiology. In this study we performed a quantitative TaqMan real-time PCR (polymerase chain reaction) analysis of enteric viruses on samples of influents and effluents from 5 wastewater treatment plants in and around Rome. Three epidemiologically important, waterborne enteric viruses were analyzed: adenoviruses, enteroviruses and noroviruses (GI and GII) and compared to classical bacterial indicators of fecal contamination. The concentration of adenoviruses was the highest, in both raw and treated waters. Mean values in influents were ranked as follows: adenovirus > norovirus GI > norovirus GII > enterovirus. In effluents, the ranking was: adenovirus > norovirus GI > enterovirus > norovirus GII. Removal efficiencies ranged from 35% (enterovirus) to 78% (norovirus GI), while removal efficiency for bacterial indicators was up to 99%. Since molecular quantification does not necessarily indicate an actual threat to human health, we proceeded to evaluate the infectivity of enterovirus particles in treated effluents through integrated cell culture and real-time PCR. Infectivity assays detected live virions in treated water, pointing to potential public health risks through the release of these viruses into the environment. A better understanding of viral presence and resistance to sewage purification processes have the potential of contributing to the effective management of risks linked to the recycling of treated wastewater, and its discharge into the environment.